ANALYSIS OF ACCURACY THE TAX OBJECT SALES VALUE (NJOP) TO MARKET VALUE WITH ASSESSMENT SALES RATIO METHOD (Case Study in Malang City) - Wardana, Rendra Kurnia (Fakultas Politik Pemerintahan, 2019)
Analysis of Accuracy The Tax Object Sales Value (NJOP) to Market Value with Assessment Sales Ratio Method. (Case Study In Malang City). This research is conducted to know the accuracy of determination of Tax Object Sales Value (NJOP) which determined by the government to current market value in society. This research was conducted in 5 (five) sub-districts in all areas of Malang City by taking samples of 80 land and building sales transactions in 2016-early 2017. This research uses a descriptive method with purposive sampling technique. The result is Assessment Sales Ratio in Kedungkandang District at 66%, Sukun District 68%, Klojen District 63%, Lowokwaru District 79%, and District Blimbing 70%. While for the entire area of Malang City of 69%. This shows that the Assessment Ratio in Malang City is still far from the standard set by IAAO that is 90% of its market value. The result of the mean divided by the median is 0.93 and the mean divided by the weighted mean of 1.13. This shows that there is no under assessment or over assessment, but it does not reflect the proportional assessment in Malang City area. COD (coefficient of dispersion) of 27.27% and COV (coefficient of variation) of 35.87% indicates that there is a need for reappraisal of NJOP which is set so as not to be too far from market value.